Relationship Between Online Game Addiction and Aggressive Behavior in Students at STIKES Persada Husada Indonesia in 2021: Aran Aran, Elwindra Elwindra - Aran, Aran; Elwindra, Elwindra (Jurnal Persada Husada Indonesia, 2021)
Aggressive behavior that is addicted to online games includes physical aggression that is shown through hitting, tends to be hit by other people or peers playing games will respond with a harder hit; and verbal aggression is generally done is threatened by issuing harsh words. This study aims to determine the relationship between online game addiction and aggressive behavior in students at STIKES PHI in 2021. This study is a quantitative study using an analytical method using a Cross Sectional approach. The research process has been carried out in May-August 2021 at STIKES PHI Bekasi. The population of this study were all students of STIKES PHI, totaling 121 students. The method used in sampling is purposive sampling as many as 107 respondents. Data analysis used in this research is univariate and bivariate analysis using Chi Square. The independent variables in this study were: gender, age, major, level, type of device, type of game, duration of day/week, duration of hours/day and online game addiction, and the dependent variable was aggressive behavior.The results showed that there was a significant relationship between gender, type of game, duration of play, online game addiction and aggressive behavior. The conclusion of the study is that students with high online game addiction tend to behave more aggressively than students with low online game addiction.